Impacts of Intraseasonal Oscillations on Tropical Cyclone Rapid Intensification in the Northwestern Pacific During Winter - Chaodong Chen; Zheng Ling; Hailun He; Tianyu Zhang (Remote Sensing)
In winter, the northwestern Pacific (NWP) is affected by two atmospheric intraseasonal oscillations (ISOs), the Madden–Julian oscillation (MJO) and the quasi-biweekly oscillation (QBWO). Using observational data and global reanalysis products, the present study investigates the impact of ISOs on the rapid intensification (RI) of tropical cyclones (TCs) in the NWP. The results indicate that both the MJO and QBWO can affect the frequency, occurrence location, intensification rate, and duration of TCRI. More (fewer) RI events occur in the convective (non-convective) phases of the MJO and the QBWO, when the main RI region is dominated by the convective (non-convective) signals of the ISOs. Additionally, the modulation of RI frequency by the MJO is much stronger than that by the QBWO. With the eastward (westward) propagation of the convective signals of the MJO (QBWO), the RI occurrence location shows a clear eastward (westward) shift. Further analysis shows that the low-level relative vorticity and mid-level relative humidity play a major role in the modulation of ISOs on RI frequency and location. To RI intensify rate and RI duration, the effects of the MJO and QBWO are relatively weak. The combined effects of the MJO and QBWO on TCRI are also discussed in this study. These findings underscore the important role of both the MJO and QBWO in modulating the TCRI.